An interpretation of creep rupture properties of grade 91 steel service- exposed for 100, 000 hours at 600 °C. (2nd January 2022) - Maruyama, K.; Yaguchi, M.; Minami, Y.; Tamura, K.; Yoshimi, K.
ABSTRACT: Creep rupture data of grade 91 steel used as hot reheat pipes have been reported recently. The data are investigated by comparison with the creep rupture database of the steel in normalised and tempered (NT) states. Four regions H, M, L and G with different values of stress exponent appear in creep of grade 91 steel. The pipes were used in long-term region G (around 600 °C for 100, 000 hours) in fossil-fired power plants. Medium- and low-stress regions M and L are confirmed to exist in the service-exposed states. Stress exponents in the two regions are kept unchanged in all the pipes, but the service exposure reduces their remaining creep rupture lives. The reduction is significant in the pipes made by cold bending. The service exposure retards the appearance of long-term region G. Causes of these findings are discussed in this paper.